ADEQUATE ANTHROPOLOGY OF KAROL WOJTYLA - M. G. Kokhanovska (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is aimed to introduce Karol Wojtyła’s anthropological teaching into the philosophical discourse through the systematization of anthropological issues in his philosophical and theological works. Provision of insight into the peculiar features of his adequate anthropology implies the fulfillment of the following tasks: first, identification of the methodology and the meaning of the principal concepts; secondly, study of the thinker’s key ideas; thirdly, presentation of the periodization of his anthropological doctrine development. Theoretical basis comprises of Karol Wojtyła’s works written before and during the pontificate, excluding his poetic writing. The fulfillment of tasks involves processing the substantial database of academic research devoted to Karol Wojtyła’s views. It will help identify less-explored issues in Karol Wojtyła’s legacy, as well as contradictory aspects in the interpretation of the thinker’s ideas. In view of the growing interest of philosophical anthropology to everyday life, this aspect of Karol Wojtyła’s teaching is an important point in the analysis of his philosophical and anthropological considerations. Therefore, general research methods and approaches will help study Karol Wojtyła’s views on the nature of a human being, as well as individual and social dimensions of a person’s life. Originality lies in systematizing Karol Wojtyła’s anthropological ideas (in particular, through the study of all the thinker’s Polish-language works excluding poetry). The disclosure of the methodology, the key concepts and their interpretations, and the periodization of the development of Karol Wojtyła’s anthropological views can reveal his connection with the philosophical trends and define his place in modern philosophy. Conclusions. Wojtyła justifies the need for a new anthropological doctrine with an inappropriate place of a human being in the value system of the modern world, as he or she has evolved from the aim of everything ever created to the means. The basis of the new doctrine of a human being, namely adequate anthropology, is, according to him, human identity, dignity and "moral greatness". Karol Wojtyła’s "new human being" is the result of an integrated approach to studying the anthropological issues of the present and the response to "cultural impoverishment" and "the decline of mankind".